Developing Students’ Talent Regarding Vocational Career since Basic Education: Theories’ Comprehension - Nurhadi, Didik; Lyau, Nyan-Myau; Zahro, Siti (Jurnal Ilmu Pendidikan, 2023)
Each countries have human resources with plenty of remarkable talents that probably have no opportunities to develop their interest to get great job opportunities in the future. Those talents may remain undiscovered unless programs for discovering and developing talents are established and opportunities are provided. To sharpen students’ sense of vocation, it is important to provide vocational education introduction for elementary school students so that the government may enhance the quality of human re-sources through developing their talents to boost their professional career. This article aims to explain how to reveal one’s talent for the vocation as early at the school age as possible and how to develop it. This study used literature review method with 107 references from international journals' articles and international books regarding vocational studies in basic’s education level.  The result showed that developing talent through vocational introduction is important to the process of unearthing, harnessing, and developing students’ talent since early from elementary school level until post-secondary level.  Eventually, this will build students' brilliant career in the future